2014
DOI: 10.1149/2.0091502jes
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline TiO2(B) as Anode Material for Sodium-Ion Batteries

Abstract: High surface area, nanostructured, and phase-pure TiO 2 (B) noodles-like secondary particles were successfully synthesized by a facile one-pot synthesis, based on the hydrolysis of TiCl 3 using a mixture of ethylene glycol and water at moderate temperature. The primary nanoparticles have a uniform size and are about 15 nm in diameter as determined by TEM analysis and exhibit an increased exposure of the (010) facet as indicated by XRD analysis. Unlike the electrochemical reaction with lithium, the application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 70 publications
5
93
2
Order By: Relevance
“…9 This phenomenon is obviously different from anatase TiO 2 and hollandite-type TiO 2 , 24,25 however, similar with rutile TiO 2 .…”
Section: +mentioning
confidence: 92%
See 3 more Smart Citations
“…9 This phenomenon is obviously different from anatase TiO 2 and hollandite-type TiO 2 , 24,25 however, similar with rutile TiO 2 .…”
Section: +mentioning
confidence: 92%
“…And then, Wu et al reported a noodle-like nanocrystalline TiO 2 (B) fabricated through hydrolysis of TiCl 3 using a mixture of ethylene glycol and water at moderate temperature for anode materials of SIBs. 9 The reversible capacity of this nanocrystalline TiO 2 (B) can reach to about 100 mA h g À1 at 33.5 mA g À1 over 70…”
Section: -5mentioning
confidence: 97%
See 2 more Smart Citations
“…22,23 However, their working potential is close to that of metallic sodium, raising serious safety concerns due to the risk of sodium plating, in analogy to graphite in LIBs. Titanium oxides, like Na 2 Ti 3 O 7 24-26 or TiO 2 polymorphs, 27,28 are receiving particular attentions due to their good rate capability and long-term cycle ability. Alloying materials, [29][30][31] or intermetallic compounds 32 offer high delivered capacities (about 400-500 mAh g −1 ).…”
mentioning
confidence: 99%